Liver health in patients with hemophilia: Residual risk factors of liver-related complications after HCV-clearance. (March 2023) - La Mura, V.; Bitto, N.; Capelli, C.; Caputo, C.; Siboni, S.; Arcudi, S.; Ciavarella, A.; Gualtierotti, R.; Fracanzani, A.L.; Sangiovanni, A.; Peyvandi, F.
Abstract : Background and Aim: HCV is highly prevalent in hemophilia. Nowadays DAA warrants 80-100% rate of sustained virological response (SVR) but no studies have described the clinical outcome post-SVR in patients with hemophilia. We conducted a prospective screening to detect any relevant risk-factor of liver-complications after HCV-clearance in this setting. Methods: 119 HCV-patients (median age:54 years;range:36-87): 108/11 hemophilia A/B. SVR was achieved after interferon-based therapies in 43 patients (36%), after DAA in 53 (45%). Twelve patients (10%) had spontaneous HCV-clearance. Any active factor of chronic liver damage was registered along with biochemistry, liver stiffness measurement (LSM) and ultrasound (US) to rule-in/out advanced fibrosis/cirrhosis. A pre/post-SVR sub-analysis was conducted in 57 patients with LSM, US, non-invasive tests of fibrosis (NITs) (e.g.FIB-4, APRI) simultaneously available to show their change. Results: Ninety-six patients (81%) presented at least one active risk-factor of chronic liver-damage, metabolic factors were the most prevalent (77%). Ten patients (8%) were HIV and 4 (4%) HBV, both infections under control at time of the screening. After our evaluation, 51 patients (43%) had US-steatosis. Twenty-one patients (18%) had clinical, biochemical, liver-morphology and/or LSM suggestive of advanced fibrosis/cirrhosis. Furthermore, 10 patients (8%) had esophageal varices, 3 (3%) hepatocellular carcinomas (HCC). One HCC was detected in a non-cirrhotic liver but associated with metabolic comorbidities, 2 HCC were Milan-out and were addressed to a down-staging approach. All HCC were finally transplanted. In the sub-analysis, LSM and NITs were reduced after SVR (p<0.05), while morphological US-signs specific of cirrhosis did not change. Overall, after HCV-clearance, 13/67 patients (19%) with LSM≤8KPa had at least one US-sign suggestive of advanced fibrosis/cirrhosis. Conclusions: Residual risk-factors of chronic liver damage after HCV-clearance are frequent. LSM and NITs significantly change after SVR and could be inaccurate to rule-out advanced fibrosis/cirrhosis. A specific diagnostic work-up is warranted to maintain liver-health in hemophilia.